2018
DOI: 10.1186/s13048-018-0382-3
|View full text |Cite
|
Sign up to set email alerts
|

Single and combined use of red cell distribution width, mean platelet volume, and cancer antigen 125 for differential diagnosis of ovarian cancer and benign ovarian tumors

Abstract: BackgroundCancer is widely believed to result from chronic inflammation, and red cell distribution width (RDW) and mean platelet volume (MPV) are considered as inflammatory markers for cancer. We investigated the values of RDW, MPV, and cancer antigen 125 (CA125), alone or in combination, for distinguishing between ovarian cancer and benign ovarian tumors.MethodsThe study included 326 patients with ovarian cancer, 290 patients with benign ovarian tumors, and 162 control subjects. Hematologic tests were perform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 28 publications
2
19
0
Order By: Relevance
“…Despite a great progress in the diagnosis and therapy of it, the survival of patients with OC is still not optimistic. 19 In our study, we verified that SNHG3, overexpressed in OC, can be adopted for diagnosis of OC, and the high expression of it indicated a poor prognosis of patients. We found that knockdown of SNHG3 could inhibit the growth of OC cells and affect the biological function of OC cells through the miR-339-5p/TRPC3 axis, which confirmed that SNHG3 is expected to be a potential marker for diagnosis, treatment and prognosis evaluation of OC.…”
Section: Discussionsupporting
confidence: 65%
“…Despite a great progress in the diagnosis and therapy of it, the survival of patients with OC is still not optimistic. 19 In our study, we verified that SNHG3, overexpressed in OC, can be adopted for diagnosis of OC, and the high expression of it indicated a poor prognosis of patients. We found that knockdown of SNHG3 could inhibit the growth of OC cells and affect the biological function of OC cells through the miR-339-5p/TRPC3 axis, which confirmed that SNHG3 is expected to be a potential marker for diagnosis, treatment and prognosis evaluation of OC.…”
Section: Discussionsupporting
confidence: 65%
“…MPV is also a useful indicator in some inflammatory diseases, and it has been associated with disease activity and severity of inflammation [18]. Released inflammatory mediators in cancer increase platelet activation, leading to a subsequent change in MPV [19]. The current study showed that MPV increased in lung cancer patients compared to healthy subjects, showing that the process of lung cancer may be associated with platelet activity and result in the variation of MPV.…”
Section: Discussionsupporting
confidence: 51%
“…The DD level seemed to outperform the CA-125 as a diagnostic biomarker, even for early stage EOC, where 73–83% of patients had elevated DD and 33–39% had elevated CA-125 [20, 22]. Interestingly, CA-125 in combinations with the red cell volume distribution width and the mean platelet volume (parameters usually measured as part of the whole blood cell count) may facilitate the early detection and differential diagnosis of ovarian cancer compared with benign ovarian tumors [58]. Measurement of serum CA-125 is routinely used to aid diagnosis and in a follow-up of patients with EOC.…”
Section: Discussionmentioning
confidence: 99%